effect of periodic vegetarianism on serum retinol and α-tocopherol levels - Sarri, Katerina; Bertsias, George; Linardakis, Manolis; Tsibinos, George; Tzanakis, Nikolaos; Kafatos, Anthony (International journal for vitamin and nutrition research, 2009)
The Greek Orthodox Christian (GOC) diet is unique in that it regularly interchanges between an omnivorous to a vegetarian type of diet over the course of the ecclesiastical year, and no study to date has focused on its impact on antioxidant vitamins A (retinol) and E (alpha-tocopherol) status. Thirty-seven strict adherents of the GOC, mainly priests and nuns, (18 males, 19 females, mean age 43.0 + or - 13.1 years), and 48 age- and sex- matched controls (21 males, 27 females; mean age 38.6 + or - 9.6 years) were studied prior (pre) and at the end (end) of the Christmas fasting (CF) period (40 days), when meat and dairy products are prohibited. Fasters had been following all dietary recommendations of the GOC for a mean of 21.2 + or - 15.7 years. Compared to the control group, fasters had higher pre- retinol and pre- alpha-tocopherol levels. Fasters reduced their retinol (-0.8 + or - 0.6 micromol/l) and alpha-tocopherol levels (-8.0 + or - 6.6 micromol/L) during the CF period, whereas controls increased them (0.3 + or - 0.7 and 0.4 + or - 4.8 micromol/L, respectively, p<0.001). Nevertheless, values in both groups were well above the lowest cut-off points. All subjects had alpha-tocopherol:total cholesterol ratio >2.25, which is a cut-off value for the anti-atherogenic influence of alpha-tocopherol. Changes of serum alpha-tocopherol and retinol within the CF period correlated positively with changes in total cholesterol (p=0.013 and p=0.017, respectively), whereas the latter was also correlated with changes in low-density lipoprotein (LDL) and total cholesterol:high-density lipoprotein (TC:HDL) ratio (p=0.021 and p=0.049, respectively). Dietary intakes of several nutrients did not correlate with concentrations of retinol and alpha-tocopherol in either study group. These results suggest that adherence to the GOC diet does not increase the risk of antioxidant vitamins A and E deficiency.